Penyuluhan Dan Pendampingan Program Perilaku Hidup Bersih Dan Sehat Di Kelurahan Banten Kecamatan Kasemen Kota Serang - Budi Hasanah; Adi Suharyanto; Dita Budiarti; Yuke Winaldha Fiscaranie (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2019)
Perilaku Hidup Bersih dan Sehat Program (PHBS) was also apply in Kelurahan Banten, Kasemen it’s not runing well because of multifactoral reason. Starting from people who did not understand what PHBS was and the difficulty of applying the clean and healthy life. It was happened because people was accustomed to apply unhealthy life. This progam was the government program to improve the health quality for person, family and society. The scope of PHBD was in the family environment. To support the counseling and coaching, an education process was needed for people who represent their families in order to improve the quality public health through counseling and mentoring. After counseling, there was accompaniment of the supplementory food supply for children who suffered malnutrition, which the disease was on of the effect of lifestyle that was not in accordance with the guideline of clean and healthy life. The supplementory food supply was done because the number of children suffering from mainutrition was in the red zone. The program was carried out in the Kelurahan Banten Office and the partner of this program was people in the Pekapuran RW 01. The method were information transfer method and assistance. The result if this service were expected to be abble to provide an overwiew and become a stimulus for society about the importance of health especially for people in Pekapuran Kelurahan Banten.Key Words : counseling, Assistance, PHBS Program